User-Centered Categorization of Mood in Fiction - (:unkn) unknown (My University, 2022)
Readers articulate mood in deeply subjective ways, yet the underlying structure of users’ understanding of the media they consume has important implications for retrieval and access. User articulations might at first seem too idiosyncratic, but organizing them meaningfully has considerable potential to provide a better searching experience for all involved. The current study develops mood categories inductively for fiction organization and retrieval in information systems.We developed and distributed an open-ended survey to 76 fiction readers to understand their preferences with regard to the affective elements in fiction. From the fiction reader responses, the research team identified 161 mood terms and used them for further categorization.Our inductive approach resulted in 30 categories, including angry, cozy, dark, and nostalgic. Results include three overlapping mood families: Emotion, Tone/Narrative, and Atmosphere/Setting, which in turn relate to structures that connect reader-generated data with conceptual frameworks in previous studies.The inherent complexity of “mood” should not dissuade us from carefully investigating users’ preferences in this regard. Adding to the existing efforts of classifying moods conducted by experts, the current study presents mood terms provided by actual end-users when describing different moods in fiction. This study offers a useful roadmap for creating taxonomies for retrieval and description, as well as structures derived from user-provided terms that ultimately have the potential to improve user experience.
Keywords: Fiction; Categories; User warrant; Mood; Affective information needs; Pleasure reading; Card sorting; Metadata